2012
DOI: 10.1021/bi300241m
|View full text |Cite
|
Sign up to set email alerts
|

Using a Fluorescent Cytosine Analogue tCo To Probe the Effect of the Y567 to Ala Substitution on the Preinsertion Steps of dNMP Incorporation by RB69 DNA Polymerase

Abstract: Residues in the Nascent Base-pair binding Pocket (NBP) of bacteriophage RB69 DNA polymerase (RB69pol) are responsible for base discrimination. Replacing Tyr567 with Ala leads to greater flexibility in the NBP, increasing the probability of misincorporation. We used the fluorescent cytosine analogue, 1,3-diaza-2-oxophenoxazine (tC°) to identify pre-insertion step(s) altered by NBP flexibility. When tC° is the templating base in a wild type (wt) RB69pol ternary complex, its fluorescence is quenched only in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Previously, Beese et al have reported a dCTP/dA mismatch that included a minor tautomer with Watson-Crick geometry at the NBP of BF. 12 If tautomerization within the pol complex involves a transient protonation/deprotonation step, 37 then rejection of protonated bases in the NBP of wt pol could also serve as a mechanism to reject tautomerization. Although, these possibilities appear to adequately account for the degree of base discrimination exhibited by wt RB69pol, they do not exclude other explanations that may prove equally valid.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Beese et al have reported a dCTP/dA mismatch that included a minor tautomer with Watson-Crick geometry at the NBP of BF. 12 If tautomerization within the pol complex involves a transient protonation/deprotonation step, 37 then rejection of protonated bases in the NBP of wt pol could also serve as a mechanism to reject tautomerization. Although, these possibilities appear to adequately account for the degree of base discrimination exhibited by wt RB69pol, they do not exclude other explanations that may prove equally valid.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it was Tsai and Johnson who proposed that base discrimination is determined by the relative magnitudes of the forward and reverse rates of the prechemistry conformational change (fingers closing) compared to the rate of the chemical step that completely changed the concept prevailing at the time concerning base selectivity . Our studies of RB69pol have shown that nucleotide insertion efficiency and base selectivity are determined by a number of factors, including interbase HBs, minor groove HBs, base stacking, the geometry of the base pair as it fits into the NBP, conformational changes, and the partitioning of the primer terminus between the pol and exo subdomains. ,,,, Subsequently, we showed that the results obtained by Tsai and Johnson also applied to RB69pol . In addition to the results obtained from kinetic and structural studies, molecular dynamics simulation approaches have further enhanced our understanding of conformational dynamics of the polymerase-catalyzed nucleotidyl transfer reaction that results in base selectivity. , We discuss each of them in turn in the following sections.…”
Section: Factors That Contribute To the Dntp Insertion Efficiency And...mentioning
confidence: 88%
“…As an independent check, another fluorescent analogue, tC°, which can form three HBs with guanine (Figure 8 C), was used in the same type of experiment. 77 The quenching of the tC° fluorescence depends on both base stacking with the penultimate base pair and hydrogen bonding with the templating base. Similar values of k –2 were obtained (S. Xia et al, unpublished results).…”
Section: Factors That Contribute To the Dntp Insertion Efficiency Andmentioning
confidence: 99%
“…The donor, tC o , was located at the n-7 position in the primer strand, and the acceptor, tC nitro , was placed at the N position of the template strand. The relative orientation of tC o -tC nitro, when embedded in the P/T is shown in Figure 4B and is modelled on our previously reported dGTP/tC o -containing structure of RB69pol (10). The resulting FRET efficiencies are shown in Table 4.…”
Section: Resultsmentioning
confidence: 99%